S‐layer proteins as an immobilization matrix for aptamers on different sensor surfaces. Issue 7 (22nd April 2015) - Weinert, Ulrike; Vogel, Manja; Reinemann, Christine; Strehlitz, Beate; Pollmann, Katrin; Raff, Johannes
<x xml:space="preserve">Abstract</x> S‐layer proteins provide a biocompatible environment with different kinds of functional groups, perfect for the sequential coupling of any kind of biofunctional molecule. In addition, their nanostructure and their ability to crystallize on surfaces in a nanometer‐thick monolayer ensure a regular arrangement of these molecules on solid supports. In this work, a thrombin‐binding aptamer and an ofloxacin‐binding aptamer were coupled with different chemical crosslinkers to S‐layer proteins using them for defined immobilization. S‐layer protein monomers and paracrystalline S‐layers were successfully modified with the thrombin‐binding aptamer. However, S‐layer protein monomers were not able to crystallize after aptamer modification and showed no thrombin binding during random surface attachment. In contrast, aptamers linked to an intact S‐layer in suspension or an S‐layer coating were still functional. The modification rate of S‐layers with the thrombin‐binding aptamer was estimated with one aptamer to two unit cells (unit cell = four monomers). Verification of the functionality of both aptamers through target binding after S‐layer‐immobilization on solid supports was proven by laser‐induced fluorescence spectroscopy (LIFS), resonant mirror sensor (IAsys), and quartz crystal microbalance with dissipation monitoring (QCM‐D), respectively. Hence, this study presents S‐layer proteins as an interesting alternative to existing immobilization matrices for recognition biomolecules.